2022
DOI: 10.1126/sciimmunol.abm5505
|View full text |Cite
|
Sign up to set email alerts
|

Innate immunological pathways in COVID-19 pathogenesis

Abstract: Coronavirus disease 2019 (COVID-19) is a disease characterized by a profound dysregulation of the innate immune system. This knowledge has emerged from the large body of single-cell omics studies of patients with COVID-19, which have provided one of the most detailed cellular atlases of a human disease ever. However, we are only beginning to understand the innate immunological pathways that govern host defense and immunopathology in COVID-19. In this review, we discuss the emerging understanding of how SARS-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(169 citation statements)
references
References 178 publications
9
158
0
2
Order By: Relevance
“…Triggering type I IFN production and release is a crucial outcome of PRR signaling, as type I IFN unleash autocrine and paracrine antiviral responses [ 30 ]. Research is currently defining the precise role of PRRs in sensing SARS-CoV-2, building on the knowledge of coronavirus infection [ 31 ]. Therefore, this contributes to the understanding of ubiquitin in antiviral signaling and defense in COVID-19 [ 32 ].…”
Section: Ubiquitylation Isgylation and Their Roles In Human Antiviral...mentioning
confidence: 99%
See 1 more Smart Citation
“…Triggering type I IFN production and release is a crucial outcome of PRR signaling, as type I IFN unleash autocrine and paracrine antiviral responses [ 30 ]. Research is currently defining the precise role of PRRs in sensing SARS-CoV-2, building on the knowledge of coronavirus infection [ 31 ]. Therefore, this contributes to the understanding of ubiquitin in antiviral signaling and defense in COVID-19 [ 32 ].…”
Section: Ubiquitylation Isgylation and Their Roles In Human Antiviral...mentioning
confidence: 99%
“…The severity of COVID-19 can widely vary between patients. Innate immune sensing and the subsequent activation of the adaptive immune response seem to play a critical role in this [ 31 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Although the protective effect of STING inhibition was not time-dependent, and was replicated with prophylactic administration 35 , we note that early TBK1 inhibition would be expected to fuel viral replication, since early type-I anti-viral responses are driven by RNA sensors, including RIG-I and MDA5 30 . However, we found that late administration of IDX did not impact the viral load measured in the lungs of SARS-CoV-2-infected mice, while concurrently dampening critical inflammatory factors associated with severe COVID-19 in patients (e.g., TNF, IL-6, and IFN-g) and decreasing airway neutrophil infiltration which correlates with disease severity [36][37][38][39][40] .…”
Section: Idronoxil Protects Against Sars-cov-2-driven Hyper-inflammationmentioning
confidence: 77%
“…It warrants that neutrophildriven innate immune response at oral mucosa initiates a dysbiotic cycle, tissue damage that ultimately leads to prolonged infection-inflammation sequelae. In severe COVID-19 cases, neutrophil degradation and NETosis in blood and lung have been functionally linked to severe inflammation and thrombosis 14,15,[47][48][49][50] . These molecular consequences of COVID-19 are now well studied.…”
Section: Discussionmentioning
confidence: 99%